Soft Tissue Reconstruction of Nasal Defects - R. K. keswani; R. C. Dadoo; H. L. Chabbra (Indian Journal of Plastic Surgery)
A large variety of soft tissue lesions of the nose are presented. The different operative procedures used are discussed, and preference for a surgical procedure in a particular situation is indicated.